(untitled) (Open Herald: Periodical of Methodical Research, 2023)
Gingival retraction is an important procedure in the fabrication of indirect restorations, which is necessary to obtain a more accurate impression. Correct enlargement of the periodontal sulcus remains one of the most important procedures. In this regard, retraction threads and retraction techniques should be selected that minimize tissue trauma and eliminate irreversible loss of soft tissue height. Gingival retraction was first reported by Thompson in 1941. Currently, many materials for this procedure are available on the dental market, with retraction threads occupying a major position among them.